Pressure Never Lies, but It Should Be Interpreted Thoughtfully: The Role of Hydrostatic Pressure in Coronary Physiology - Kőszegi, Zsolt; Szabó, Gábor Tamás (Journal of personalized medicine, 2024)
Personalized medicine shows promise for the management of patients with coronary artery disease (CAD) [...].Personalized medicine shows promise for the management of patients with coronary artery disease (CAD) [...].